Law Enforcement of Criminal Trading of Narcotics by the North Sumatera Narcotics Agency - Ridzwan Budiadi; Eriska Englin Sofia Butarbutar; Rony Parlungutan Tampubolon (Musamus Law Review, 2020)
The circulation of narcotics is one of the problems that should get more attention in Indonesia, especially in the city of Medan. This study uses the juridical-normative method in explaining research questions. In reinforcing arguments and explanations, researchers used primary data through direct interviews with the North Sumatra National Narcotics Agency (BNN) and secondary through scientific writings, news and official government publications. This paper explains that the government must be able to enforce the law related to the crime of narcotics trafficking, this is due to the large impact that can arise from the destruction of Indonesia's young generation.